Ethnobotanical study of medicinal plants traditionally used in the Arribes del Duero, western Spain. - González, José a; García-Barriuso, Mónica; Amich, Francisco (Journal of ethnopharmacology, 2010)
Aim of the study: We studied traditional knowledge (TK) and current uses of medicinal plants among the inhabitants of the Arribes del Duero–ARD–(Spain), documenting traditional medical practices. Materials and methods:We interviewed 80 key informants (44 men and 36 women). Their average age was 72 years (range 48–98 years). We calculated the cultural importance for each species cited. To analyze how TK varies with the characteristics of the different informants, we performed an ANCOVA, taking the number of use-reports (URs) provided by each informant as a variable to model, and age and gender as explanatory variables. Results and conclusions: 156 medicinal remedies were recorded; they were based on a single species and were cited by at least three independent informants, and half of them are still in use today. These remedies are related to nine major organ systems and 54 therapeutic uses, and 70 species (belonging to 39 families) are used, most of which are herbs (64%). The most relevant family is the Lamiaceae (23 remedies, 8 species) and the species employed in the greatest number of remedies (8) is Urtica dioica L. However, the taxon with the greatest cultural value is Hypericum perforatum L. (CI = 0.71). 31% of the variability of the TK can be explained in terms of the age and gender of the informants (R 2 = 0.315), the age factor having a positive effect. Most of the remedies are related to the treatment of unimportant ailments, referring to disorders of the skin, and the respiratory and digestive systems. The leaves and fruits are the most frequently sought plant parts (40 and 17% of the plants mentioned, respectively), and infusions (34%) and decoctions (28%) are the main methods used for preparing the remedies. Likewise, we recorded remedies based on plant mixtures and ethnomedicinal novelties or rare uses, and comment on the inﬂuence exerted by superstition. Currently, many people preserve a rich TK about medicinal plants, and it may be afﬁrmed that the folk medicine is still very much alive in the ARD, above all as regards the treatment of certain common afﬂictions or unimportant ailments.
The following values have no corresponding Zotero field: accession-num: 20643201
Keywords: Ethnobotany; Medicinal plants; Quantitative analysis; Traditional remedies

Pharmaceutical ethnobotany in the western part of Granada province (southern Spain): ethnopharmacological synthesis. - Benítez, G.; González-Tejero, M. R.; Molero-Mesa, J. (Journal of ethnopharmacology, 2010)
The aim of this work is to catalogue, document, and make known the uses of plants for folk medicine in the western part of the province of Granada (southern Spain). An analysis was made of the species used, parts of the plant employed, preparation methods, administration means, and the ailments treated in relation to pathological groups. Materials and methods: The work was performed in 16 municipalities within the study zone. The partici- pants were located mainly by questionnaires distributed in public and private centres. The information, gathered through semi-structured open interviews of a total of 279 people, was included in a database for subsequent analysis.Afloristic catalogue of the territorywascompiled, enabling analyses of the relevance of certain botanical families in popular medicine. Results and conclusions: Great diversity was established among medicinal species in the region. A total of 229 species of plants were catalogued for use in human medicine to prevent or treat 100 different health problems covering 14 different pathological groups. The number of references reached 1963. The popular pharmacopoeia of this area relies primarily on plants to treat digestive, respiratory, and circulatory problems, using mainly the soft parts of the plant (leavesandflowers)prepared in simpleways (decoction, infusion). An analysis of the medicinal ritual uses of 34 species and the different symptoms reflected a certain acculturation in relation to ethnobotanical knowledge in the last 20 years. Ethnopharmacological relevance: The traditional knowledge of plants was shown in relation to medicinal use, reflecting a striking diversity of species and uses, as well as their importance in popular plant therapy in the study zone. These traditions could pave the way for future phytochemical and pharmacological studies and thereby give rise to new medicinal resources.
The following values have no corresponding Zotero field: accession-num: 20226847
Keywords: Acculturation; Ethnopharmacology; Folk medicine; Granada; Medicinal plants; Spain

Medicinal plants in the Mediterranean area: synthesis of the results of the project Rubia. - González-Tejero, M R; Casares-Porcel, M; Sánchez-Rojas, C P; Ramiro-Gutiérrez, J M; Molero-Mesa, J; Pieroni, A; Giusti, M E; Censorii, E; de Pasquale, C; Della, a; Paraskeva-Hadijchambi, D; Hadjichambis, a; et al. (Journal of ethnopharmacology, 2008)
Within the scope of the European project RUBIA (ICA3-2002-10023), research has been performed on the traditional use and handling of plant species in several Mediterranean countries, Albania, Algeria, Cyprus, Egypt, Italy, Morocco, and Spain. This paper synthesises the chief results related to the medicinal utilization of those plants.
Keywords: Ethnobotany; Medicinal; Medicinal plants; Mediterranean; Mediterranean Region; Plants; Species Specificity

Ethnobotany of Montseny biosphere reserve (Catalonia, Iberian Peninsula): plants used in veterinary medicine. - Bonet, M. Angels; Vallès, Joan (Journal of ethnopharmacology, 2007)
The present paper deals with plants used in veterinary medicine in Montseny. An ethnobotanical survey was carried out in the Montseny massif, which is situated in north-east Catalonia (Iberian Peninsula), covers 826 km(2) and has a population of 80,000. The information was obtained through 120 ethnobotanical interviews to 180 informants. Out of 584 species reported, 351 are claimed to be used in the health field (human and veterinary medicine), 280 in human and animal food and 236 have another kind of popular use. Medicinal species represent around 16.5% of Montseny's vascular flora. In a previous paper we addressed plant use in human medicine, and the present paper deals with veterinarian uses. As a reflection of the importance of rural life in the region, at least until recent times, a substantial number of medicinal plants (89 species, representing 6% of the flora of the territory and 6.4% of all medicinal use-reports in the region) is used in veterinary medicine. These remedies are mostly for cows, calves, sheep, pigs and horses, and secondarily, to poultry, rabbits and dogs. The main ailments treated are postnatal problems, intestinal troubles, wounds and dermatological problems. In many cases, the use of these remedies in veterinary medicine is fully consistent with their use in human medicine.
The following values have no corresponding Zotero field: accession-num: 17059874
Keywords: Catalonia; Ethnobotany; Ethnoveterinary; Medicinal plants; montseny; Traditional knowledge

Ethnobotany of Montseny biosphere reserve (Catalonia, Iberian Peninsula): plants used in veterinary medicine. - Bonet, M Angels; Vallès, Joan (Journal of ethnopharmacology, 2007)
The present paper deals with plants used in veterinary medicine in Montseny. An ethnobotanical survey was carried out in the Montseny massif, which is situated in north-east Catalonia (Iberian Peninsula), covers 826 km(2) and has a population of 80,000. The information was obtained through 120 ethnobotanical interviews to 180 informants. Out of 584 species reported, 351 are claimed to be used in the health field (human and veterinary medicine), 280 in human and animal food and 236 have another kind of popular use. Medicinal species represent around 16.5% of Montseny's vascular flora. In a previous paper we addressed plant use in human medicine, and the present paper deals with veterinarian uses. As a reflection of the importance of rural life in the region, at least until recent times, a substantial number of medicinal plants (89 species, representing 6% of the flora of the territory and 6.4% of all medicinal use-reports in the region) is used in veterinary medicine. These remedies are mostly for cows, calves, sheep, pigs and horses, and secondarily, to poultry, rabbits and dogs. The main ailments treated are postnatal problems, intestinal troubles, wounds and dermatological problems. In many cases, the use of these remedies in veterinary medicine is fully consistent with their use in human medicine.
Keywords: Catalonia; Ethnobotany; Ethnoveterinary; Medicinal plants; montseny; Traditional knowledge

Folk phytotherapeutical plants from Maratea area (Basilicata, Italy). - Guarrera, Paolo Maria; Salerno, Giovanni; Caneva, Giulia (Journal of ethnopharmacology, 2005)
Field ethnobotanical survey was undertaken for the period of 2002-2003 in the Tyrrhenian part of the Basilicata region of southern Italy. Data of 56 species of plants belonging to 29 families where gathered through interviews; among the species, 47 are used in human therapy, 6 as insect repellents, 15 in veterinary medicine, 1 for its ichthyotoxic properties and 3 for magic therapeutic purposes. The most important findings in ethnomedicine relate to Nasturtium officinale (renal colic, liver diseases), Foeniculum vulgare subsp. piperitum (mouth ulcers), Leopoldia comosa (toothache, headache), Micromeria graeca subsp. graeca (coughs) and Ceterach officinarum (malaria), while in the ethnoveterinary field, we have Pteridium aquilinum (wolf bites) and Spartium junceum (fractures of animal limbs).
Keywords: Abdominal Pain; Abdominal Pain: drug therapy; Anthelmintics; Anthelmintics: therapeutic use; Antiparasitic plants; Basilicata; Common Cold; Common Cold: drug therapy; Cough; Cough: drug therapy; Diuretics; Diuretics: chemistry; Diuretics: therapeutic use; Ethnobotany; Ethnopharmacology; Ethnopharmacology: methods; Furunculosis; Furunculosis: drug therapy; Geography; Humans; Italy; Lung Diseases; Lung Diseases: drug therapy; Medicinal; Medicinal plants; Medicinal: classification; Medicine; Phytotherapy; Plant Preparations; Plant Preparations: therapeutic use; Plants; Skin Diseases; Skin Diseases: drug therapy; Time Factors; Traditional; Veterinary plants; Wound Healing; Wound Healing: drug effects; Wounds and Injuries; Wounds and Injuries: drug therapy

Ethnopharmacology of ogliastra (villagrande strisaili, sardinia, Italy). - Loi, M. C.; Poli, F.; Sacchetti, G.; Selenu, M. B.; Ballero, M. (Fitoterapia, 2004)
The use of medicinal and aromatic plants was investigated in a group of 200 elderly people (60-104-year-old) from Villagrande Strisaili (Ogliastra, Sardinia, Italy), recording the use of 78 species for the treatment of various ailments, especially of the respiratory tract, the mouth, and the skin. Seventeen plants had never been described as medicinal species in peninsular Italy, while a few others turn out to have an original use for Sardinia.
The following values have no corresponding Zotero field: accession-num: 15158984
Keywords: Italy; Medicinal plants; ogliastra; Sardinia; Traditional phytotherapy; Villagrande Strisaili

Effect of Tannins from Quercus suber and Quercus coccifera Leaves on Ethanol-Induced Gastric Lesions in Mice - Khennouf, Seddik; Benabdallah, Hassiba; Gharzouli, Kamel; Amira, Smain; Ito, Hideyuki; Kim, Tae-Hoon; Yoshida, Takashi; Gharzouli, Akila (Journal of Agricultural and Food Chemistry, 2003)
The gastroprotective effects of 70% acetone extracts of Quercus suber and Quercus coccifera leaves and of tannins (pedunculagin, castalagin, phillyraeoidin A, and acutissimin B) purified from these extracts were examined in the mouse using the ethanol-induced gastric ulcer model. Both extracts (25, 50, and 100 mg/kg), given orally, prevented the formation of ethanol-induced lesions in the stomach. The percent protection varied between 68 and 91%. Purified tannins (50 mg/kg) were also effective in protecting the stomach against ethanol, and the percent protection varied from 66 to 83%. Castalagin was the most potent. Both extracts and all of the tannins tested (10, 25, and 50 ?g/mL) strongly inhibited (55?65%) the lipid peroxidation of rabbit brain homogenate. These results suggest that the gastroprotective effects of extracts of Q. suber and Q. coccifera leaves and the purified tannins in this experimental model are related to their anti-lipoperoxidant properties. Keywords: Experimental gastric ulcer; lipid peroxidation; medicinal plants; Quercus sp.; tannins; castalagin
From Duplicate 2 (Effect of Tannins from Quercus suber and Quercus coccifera Leaves on Ethanol-Induced Gastric Lesions in Mice - Khennouf, Seddik; Benabdallah, Hassiba; Gharzouli, Kamel; Amira, Smain; Ito, Hideyuki; Kim, Tae-Hoon; Yoshida, Takashi; Gharzouli, Akila)
Keywords: Acetone; Animals; Biphenyl Compounds; castalagin; Catechols; Catechols: therapeutic use; Ethanol; Experimental gastric ulcer; Hydrolyzable Tannins; lipid peroxidation; Lipid Peroxidation: drug effects; Male; Medicinal plants; Mice; Plant Extracts; Plant Extracts: chemistry; Plant Extracts: therapeutic use; Plant Leaves; Plant Leaves: chemistry; Quercus; Quercus sp.; Quercus: chemistry; Rabbits; Stomach Ulcer; Stomach Ulcer: chemically induced; Stomach Ulcer: prevention & control; Tannins; Tannins: pharmacology; Tannins: therapeutic use

Studies on pharmaceutical ethnobotany in the regions of L'Alt Empordà and Les Guilleries (Catalonia, Iberian Peninsula). - Bonet, M a; Parada, M; Selga, A; Vallès, J (Journal of ethnopharmacology, 1999)
An ethnobotanical survey was carried out in two regions (L'Alt Emporda and Les Guilleries), situated in North East Catalonia (Iberian Peninsula), with an approximate area of 800 km2 and a population of 68000. Through interviews with 73 people, data was obtained on the medicinal uses of 220 species. The most important findings are presented here concerning the ethnopharmacology of those areas. One hundred and ninty four unreported or uncommon uses corresponding to 101 plant species were detected.
Keywords: Catalonia; Ethnobotany; Folk medicine; Medicinal plants; Quantitative ethnobotany

Contribution to the knowledge of the pharmaceutical ethnobotany of La Segarra region (Catalonia, Iberian Peninsula). - Raja, D; Blanché, C; Vallès Xirau, J (Journal of ethnopharmacology, 1997)
An ethnobotanical survey was carried out in the region known as La Segarra, situated at the north east of the Iberian Peninsula, in the inner plains of Catalonia, with an area of 720 km2 and a population of 17000. Working with 29 people, data on uses of 142 species belonging to 54 botanical families were obtained and presented, of which 13 uses corresponding to nine plant species were previously unreported.
Keywords: Catalonia; Ethnobotany; Folk medicine; Medicinal plants

Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F. M.; Suarez, M. a; Pérez, A. (Journal of ethnopharmacology, 1997)
A study of the wild and cultivated medicinal plants used in the Barros Area (southern Spain) is reported, 48 plants distributed among 20 different families are used in the treatment of various human diseases. The use of Bellis annua L. Centaurea ornata Wild., Leuzea conifera (L.) DC., Pulicaria paludosa Link and Asparagus aphyllus L. is reported.
From Duplicate 2 (Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F M; Suarez, M a; Pérez, A)From Duplicate 2 (Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F M; Suarez, M a; Pérez, A)The following values have no corresponding Zotero field: accession-num: 9032619
Keywords: Data Collection; Humans; Medicinal; Medicinal plants; Medicinal: classification; Medicine; Phytotherapy; Plants; southern Spain; Spain; Structure-Activity Relationship; Traditional; Traditional phytotherapy

Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F M; Suárez, M A; Pérez, A (Journal of ethnopharmacology, 1997)
A study of the wild and cultivated medicinal plants used in the Barros Area (southern Spain) is reported, 48 plants distributed among 20 different families are used in the treatment of various human diseases. The use of Bellis annua L. Centaurea ornata Wild., Leuzea conifera (L.) DC., Pulicaria paludosa Link and Asparagus aphyllus L. is reported.
From Duplicate 2 (Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F M; Suarez, M a; Pérez, A)
Keywords: Data Collection; Humans; Medicinal; Medicinal plants; Medicinal: classification; Medicine; Phytotherapy; Plants; southern Spain; Spain; Structure-Activity Relationship; Traditional; Traditional phytotherapy

Quantitative ethnopharmacological study of the Campidano Valley and Urzulei district, Sardinia, Italy. - Bruni, a; Ballero, M; Poli, F (Journal of ethnopharmacology, 1997)
A new method has been developed for quantitative, phytotherapeutical analysis with a goal to create a general tool suitable for a wide range of research situations. This tool would allow one to gather data in such a format as to facilitate comparison with studies from other areas. The method was applied to data gathered from two sites in Sardinia, Italy (Campidano and Urzulei). Analysis was performed on 2635 responses (a) by plant, (b) by plant part, (c) by medicinal preparation and (d) by therapeutic use. This yielded specificity indexes which proved useful in comparing phytotherapeutic applications in the two geographic areas under study. In Urzulei the original phytotherapeutic heritage is deeply rooted in the local socio-economic history and clearly reflects the area's geographic isolation. Indeed, in this area, there is little reliance on modern health care. On the other hand, in Campidano, the body of phytotherapeutic application is more extensive. Indeed, due to migration-and to a lesser extent isolation- the latter area has been more affected by technological interference and cultural overlapping. In this area attention is widely focused on such modern ailments as glycemia, hypertension and constipation.
Keywords: Medicinal plants; Quantitative ethnopharmacology; Sardinia; Traditional phytotherapy

Quantitative ethnopharmacological study of the Campidano Valley and Urzulei district, Sardinia, Italy. - Bruni, a; Ballero, M.; Poli, F. (Journal of ethnopharmacology, 1997)
A new method has been developed for quantitative, phytotherapeutical analysis with a goal to create a general tool suitable for a wide range of research situations. This tool would allow one to gather data in such a format as to facilitate comparison with studies from other areas. The method was applied to data gathered from two sites in Sardinia, Italy (Campidano and Urzulei). Analysis was performed on 2635 responses (a) by plant, (b) by plant part, (c) by medicinal preparation and (d) by therapeutic use. This yielded specificity indexes which proved useful in comparing phytotherapeutic applications in the two geographic areas under study. In Urzulei the original phytotherapeutic heritage is deeply rooted in the local socio-economic history and clearly reflects the area's geographic isolation. Indeed, in this area, there is little reliance on modern health care. On the other hand, in Campidano, the body of phytotherapeutic application is more extensive. Indeed, due to migration-and to a lesser extent isolation- the latter area has been more affected by technological interference and cultural overlapping. In this area attention is widely focused on such modern ailments as glycemia, hypertension and constipation.
The following values have no corresponding Zotero field: accession-num: 9254113
Keywords: Medicinal plants; Quantitative ethnopharmacology; Sardinia; Traditional phytotherapy

Aproveitamento de plantas espontâneas (aromáticas e mediciais), em montado de sobro - Lopes Borges, A. E.; Afonso Morais, M. H.; Bernardo, A.; Azevedo Gomes, A.; Saraiva Lopes, A. M. (Scientia gerundensis, 1992)
In a previous paper the phenological evolution of aromatic and medicinal species in the understory of open forest of cork oak was studied, localised in two <<vis-a-visn hillsides with NW and SE exposition in Odemira. In this paper the effect of exposition in biological cycle of species is apreciated. A comparative analysis between the vegetation of the two stations was made in funtion of the phenological evolution, biomass prodution, floristic list and recovery by species. The characteristic of the organic and inorganic fractions are emphasized related with the present phenophases.
Keywords: aromatic plants; biomass; cork-oak stands; Medicinal plants; Phenology

Aproveitamento de plantas espontâneas (aromáticas e mediciais), em montado de sobro - Lopes Borges, A E; Afonso Morais, M H; Bernardo, A; Azevedo Gomes, A; Saraiva Lopes, A M (Scientia gerundensis, 1992)
In a previous paper the phenological evolution of aromatic and medicinal species in the understory of open forest of cork oak was studied, localised in two <<vis-a-visn hillsides with NW and SE exposition in Odemira. In this paper the effect of exposition in biological cycle of species is apreciated. A comparative analysis between the vegetation of the two stations was made in funtion of the phenological evolution, biomass prodution, floristic list and recovery by species. The characteristic of the organic and inorganic fractions are emphasized related with the present phenophases.
Keywords: aromatic plants; biomass; cork-oak stands; Medicinal plants; Phenology